2014
DOI: 10.1186/s13059-014-0513-0
|View full text |Cite
|
Sign up to set email alerts
|

TET1 regulates hypoxia-induced epithelial-mesenchymal transition by acting as a co-activator

Abstract: BackgroundHypoxia induces the epithelial-mesenchymal transition, EMT, to promote cancer metastasis. In addition to transcriptional regulation mediated by hypoxia-inducible factors, HIFs, other epigenetic mechanisms of gene regulation, such as histone modifications and DNA methylation, are utilized under hypoxia. However, whether DNA demethylation mediated by TET1, a DNA dioxygenase converting 5-methylcytosine, 5mC, into 5-hydroxymethylcytosine, 5hmC, plays a role in hypoxia-induced EMT is largely unknown.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 38 publications
(68 reference statements)
7
114
1
Order By: Relevance
“…Hypermethylation can therefore have context-dependent effects on gene expression, leading to up-or downregulation of canyon-associated genes (see Table S3 in the supplemental material). In addition, especially for Tet1, gene-regulatory functions (repressive and activating) independent of its enzymatic activity have been described (41,42). This might in part account for Tet-dependent effects on gene expression that are apparently not correlated with hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation can therefore have context-dependent effects on gene expression, leading to up-or downregulation of canyon-associated genes (see Table S3 in the supplemental material). In addition, especially for Tet1, gene-regulatory functions (repressive and activating) independent of its enzymatic activity have been described (41,42). This might in part account for Tet-dependent effects on gene expression that are apparently not correlated with hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…TET1 also interacts with the SIN3A co-repressor complex leading to transcriptional repression of many TET1-targeted genes. [29][30][31] TET2 and TET3 can interact with O-GlcNAc transferase (OGT), and these interactions promote GlcNAcylation and increase H3K4me3 through the SET1/ COMPASS complex. 32 Non-catalytic activities of TETs cause that except tumor-suppressing function they also have tumor-promoting function.…”
Section: Discussionmentioning
confidence: 99%
“…TET hydroxylates 5-methylcytosine to generate 5-hydroxymethylcytosine, 5-formylcytosine, and 5-carboxycytosine in the consecutive biochemical reactions [85]. It has been reported that TET1 functions as a HIF coactivator and controls HIF-1-dependent epithelial-mesenchymal transition in breast cancer cells [86]. The protein interaction of TET1 with HIF-1α and HIF-2α, but not its DNA demethylase activity, is critical for HIF activation.…”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Eramentioning
confidence: 99%